Asymmetric hybridization and gene flow between Joshua trees (Agavaceae: Yucca) reflect differences in pollinator host specificity. Issue 2 (28th November 2012) - Starr, Tyler N.; Gadek, Katherine E.; Yoder, Jeremy B.; Flatz, Ramona; Smith, Christopher I.
Abstract The angiosperms are by far the largest group of terrestrial plants. Their spectacular diversity is often attributed to specialized pollination. Obligate pollination mutualisms where both a plant and its pollinator are dependent upon one another for reproduction are thought to be prone to rapid diversification through co‐evolution and pollinator isolation. However, few studies have evaluated the degree to which pollinators actually mediate reproductive isolation in these systems. Here, we examine evidence for hybridization and gene flow between two subspecies of Joshua tree (Yucca brevifolia brevifolia and Yucca brevifolia jaegeriana) pollinated by two sister species of yucca moth. Previous work indicated that the pollinators differ in host specificity, and DNA sequence data suggested asymmetric introgression between the tree subspecies. Through intensive sampling in a zone of sympatry, a large number of morphologically intermediate trees were identified. These included trees with floral characters typical of Y. b. jaegeriana, but vegetative features typical of Y. b. brevifolia. The opposite combination—Y. b. brevifolia flowers with Y. b. jaegeriana vegetative morphology—never occurred. Microsatellite genotyping revealed a high frequency of genetically admixed, hybrid trees. Coalescent‐based estimates of migration indicated significant gene flow between the subspecies and that the direction of gene flow matches differences in pollinator host fidelity. The data suggest that pollinator behaviour determines the magnitude and direction of gene flow between the two subspecies, but that specialized pollination alone is not sufficient to maintain species boundaries. Natural selection may be required to maintain phenotypic differences in the face of ongoing gene flow.